The Jews in Christian Europe : a source book, 315-1791 - Marcus, Jacob Rader, 1896-1995; Saperstein, Marc (Hebrew Union College Press : University of Pittsburgh Press, 2015)
"First published in 1938, Jacob Rader Marcus's The Jews in The Medieval World has remained an indispensable resource for its comprehensive view of Jewish historical experience from late antiquity through the early modern period, viewed through primary source documents in English translation. In this new work based on Marcus's classic source book, Marc Saperstein has recast the volume's focus, now fully centered on Christian Europe, updated the work's organizational format, and added seventy-two new annotated sources. In his compelling introduction, Saperstein supplies a modern and thought-provoking discussion of the changing values that influence our understanding of history, analyzing issues surrounding periodization, organization, and inclusion. Through a vast range of documents written by Jews and Christians, including historical narratives, legal opinions, martyrologies, memoirs, polemics, epitaphs, advertisements, folktales, ethical and pedagogical writings, book prefaces and colophons, commentaries, and communal statutes, The Jews in Christian Europe allows the actors and witnesses of events to speak for themselves"--